Tethered balloon measurements during Arctic autumn conditions in the framework of HALO-(AC)3 - Lonardi, M.; Ehrlich, A.; Schäfer, M.; Thoböll, J.; Wendisch, M. (Universität Leipzig, 2022)
The BalloonbornE moduLar Utility for profilinG the lower Atmosphere (BELUGA) was deployed in autumn 2021 in the Arctic at the AWIPEV research station in Ny-Ålesund (Svalbard). In-situ profiles of thermodynamic parameters, broadband radiation, turbulence, aerosol particle concentrations, and cloud microphysical structure, were performed. Additionally, samples of ice nucleating particles were collected. Thermal infrared radiation profiles are presented for different cloud conditions. The data provides the base for studying the vertical distribution of cloud radiative effects, and extends the common view of the bi-modal distribution of the Arctic surface energy budget. Das Fesselballonsystem BalloonbornE moduLar Utility for profilinG the lower Atmosphere (BELUGA) wurde im Herbst 2021 an der Forschungsstation Ny-Ålesund in der Arktis eingesetzt. Es wurden In-situ Profile von thermodynamischen Parametern, breitbandiger Strahlung, Turbulenz, Aerosolpartikelkonzentrationen und der mikrophysikalischer Wolkenstruktur erstellt. Zusätzlich wurden Proben von eiskeimbildenden Partikeln gesammelt. Strahlungsprofile wurden unter verschiedenen Wolkenbedeckungen gemessen und quantifizieren die vertikale Verteilung der Wolkenstrahlungseffekte. Die Profilmessungen erweitern damit die für bodennahe Messungen bekannte modale Verteilung des Energiehaushalts der Arktis.